Geriatric Health Care During the COVID-19 Pandemic: Managing the Health Crisis - Zhu Y; Liu Y; Jiang H (Clinical Interventions in Aging, 2022)
Yingqian Zhu,1,2,* Yue Liu,1,2,* Hua Jiang1,2 1Department of Geriatrics, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, 200123, People’s Republic of China; 2Department of General Medicine, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, 200123, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hua Jiang, Email huajiang2013@tongji.edu.cnAbstract: COVID-19 pandemic significantly threatens the health and well-being of older adults. Aging-related changes, including multimorbidity, weakened immunity and frailty, may make older people more susceptible to severe infection and place them at higher risk of morbidity and mortality from COVID-19. Various quarantine measures have been implemented to control the spread of COVID-19. Nevertheless, such social distancing has disrupted routine health care practices, such as accessibility of medical services and long-term continuous care services. The medical management of older adults with multimorbidity is significantly afflicted by COVID-19. Older persons with frailty or multiple chronic disease may poorly adapt to the altered health care system, having detrimental consequences on their physical and mental health. COVID-19 pandemic has posed great challenges to the health of older adults. We highlighted the difficulties and obstacles of older adults during this unprecedented time. Also, we provided potential strategies and recommendations for actions to mitigate the COVID-19 pandemic threats. Certain strategies like community primary health care, medication delivery and home care support are adopted by many health facilities and caregivers, whereas other services such as internet hospital and virtual medical care are promoted to be accessible in many regions. However, guidelines and policies based on high-quality data are still needed for better health promotion of older groups with increasing resilience during the COVID-19 pandemic.Keywords: COVID-19, older adults, health care promotion, chronic diseases, primary health care, telemedicine